Design Wind Speed for Buildings and Facilities With Non-Standard Design Life in Canadian Wind Climates - Li, Si Han (Frontiers in Built Environment, 2022)
The design life can be longer than 50 years for critical structures or infrastructures and shorter than 50 years for non-residential structures or construction periods. Some building codes provide methods to derive factors for adjusting the design wind speeds for construction periods. Eurocode 1 provides a probability factor for calculating the design wind speeds for a specific return period regulated for a construction period of less than 1 year. The Australian ABCB Temporary Structures standard provides design wind speed for construction using a different assumption. The ASCE 37 in the USA provides design wind speed reduction factors for a design life less than 5 years by maintaining the probability of exceedance of the factored wind load for 50-year design life the same for a shorter design life. These approaches can result in different results and deserve some comparisons. The present study included another method that maintains the structural reliability of the non-standard design life the same as the structural reliability for the design life of 50 years. The derived factors for a design life shorter than 50 years using these methods were compared considering the Canadian wind climates. The calculated design wind speed adjustment factors for design life longer than 50 years were evaluated using various techniques and compared with the commonly used importance factors. The present study also characterized the directionality and seasonality of the Canadian wind climates.